Aloe sin, aloin and aloe- emodin pro duc tion in Aloe vera L. calli - Matos Acurero, íngela (Ciencia, 1970)
Aloe vera L. (A. barbad ensis Mill.) belongs to the Aloaceae family and actually is a commercial and medicinal important plant because of the secondary metabolites produced. Aloesin, aloin and aloe-emodin (oxidative product of aloin) are the most important secondary metabolites not only due to the medicinal and cosmetic properties but also due to their physiological role. In this sense, it has been quantified the production of those three metabolites using different in vitro explants comparing with fresh leaves of en tire Aloe vera plants. It has observed that aloe sin production was higher in basal calli grown on medium MS1 with 1 mg.l-1 2,4-D and 5 mg.l-1 BA, while aloin con tent was higher in leaves of en tire plants. Aloe- emodin production was greater than the aloin both in basal and fresh leaves calli com pared to en tire leaves. Probably, this high aloe-emodin production found was due to the aloin oxidation. These results showed that calli cultures represent a promising source for A. vera secondary metabolites production